Reduction of torque pulsation and noises in PMSM with hybrid filter topology - Adam, Ali Ahmed; Gulez, Kayhan (ELSEVIER, 2011)
In this paper a hybrid filter topology is proposed to reduce torque pulsation switching voltage harmonics and EMI noises in PMSM with direct torque hysteresis controllers The filter topology consists of IGBT-based active filter (AF), LC filter in the main Inverter output and trap filter in the motor side The coupling of the AF-compensated voltage and the motor main voltage is achieved through series transformer The AF is characterized by detecting the harmonics in the motor phase voltages and uses hysteresis voltage control method to provide almost sinusoidal voltage to the motor windings The active filter uses hysteresis voltage controller while the motor main circuit uses hysteresis direct torque control The simulation results of this combined control structure show considerable torque ripple or pulsation reduction in steady state range and adequate dynamic torque performance as well as considerable harmonics and EMI noise reduction (C) 2010 Elsevier B V All rights reserved
Keywords: Active power filter; Direct torque control; Hybrid filters; Permanent magnet synchronous motor; Passive filters; Torque ripple; Torque pulsation; Harmonics; DRIVES; MODE; Computer Science